Electrochemical detection of TNT at cobalt phthalocyanine mediated screen-printed electrodes and application to detection of airborne vapours - Caygill, J. S.; Collyer, Stuart D.; Holmes, Joanne L.; Davis, Frank; Higson, Seamus P. J. (Wiley-Blackwell, 2013)
We describe the use of cobalt phthalocyanine as a mediator to improve the sensitivity for the electrochemical detection of TNT. Commercial screen-printed electrodes containing cobalt phthalocyanine were employed for determination of TNT. Improved sensitivities compared to screen-printed carbon electrodes without phthalocyanine were observed, current response for cyclic voltammetric measurements at modified electrodes being at least double that of unmodified electrodes. A synergistic effect between oxygen and TNT reduction was also observed. Correlation between TNT concentrations and sensor output was observed between 0–200 µM TNT. Initial proof-of-concept experiments combining electrochemical determinations, with the use of an air-sampling cyclone, are also reported.
Keywords: TNT; Cyclic voltammetry; Air sampling; Cyclone; Electrochemistry